Implementasi Augmented Reality Sebagai Media Pembelajaran Untuk Pengenalan Buah-Buahan - Rahman Nur Syam; Sigit Sugiyanto; Tito Pinandita; Feri Wibowo (Sekawan Institut, 2025)
Innovative and interactive teaching strategies have emerged as a result of the development of communication and information technology. One of the most promising and rapidly expanding educational technologies is augmented reality. By displaying virtual things in three dimensions in a real-world setting in real time, Augmented Reality can make studying more engaging and joyful for students Augmented reality can display virtual objects in three dimensions in real time, creating a more engaging and enjoyable learning experience for students. This research aims to develop and implement Augmented Reality-based fruit recognition learning media as an alternative to conventional, static and unengaging media for elementary school students, helping them visualize the concepts being learned. The Multimedia Development Life Cycle (MDLC), which has six stages concept, design, gathering materials, assembly, testing, and distribution the development methodology. This application is designed to display various types of fruit as 3D objects that can be scanned through markers using the camera on an android device. Each fruit is equipped with its own name and information to improve student knowledge. Testing is carried out through black box testing to evaluate system functions, and user feasibility testing using a Likert scale questionnaire given to 15 grade students. According to the results of black-box testing, there were no system or functional issues and the application operated as planned. It received an 84.86% feasibility score, placing it in the